Framework and Prototype Development of Mathsci Instruments for Measuring 21st Century Skills in Islamic Context - Zulfiani Zulfiani; Iwan Permana Suwarna; Abdul Muin (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2021)
AbstractThe development of competency assessments that measure 21st century competencies is critical for improving the quality of education. The purpose of this research is to describe a framework and prototype for assessing Math and Science or Math-Sci competency skills in the twenty-first century. The method of development research employed in this study is based on the Akker framework, which entails preliminary research, prototyping, design, and development in a paper and pencil test format. The equipment of the investigation included observation sheets, questionnaires, and tests. This study results in a conceptual framework for the instrument and a verified prototype of the Math-Sci competence evaluation. The Math-Sci competence evaluation is conceptualized around thematic, interdisciplinary questions that integrate three (three) subjects, namely Science (Biology-Physics) and Mathematics, in an Islamic context. Math-Sci, using the ladder analogy (monodisciplinary, interdisciplinary 1, and interdisciplinary 2) to rank students' competency, relates to the thought process of Bloom's taxonomy, the context, and the complexity of the topic. The instrument created was deemed valid and practicable based on the results of expert validation. The development of the Math-Sci competence assessment instrument was the first step toward strengthening assessment for learning and assisting in the improvement of learning through the presentation of integrated contextual problems. AbstrakPengembangan asesmen kompetensi yang membekalkan kecakapan abad 21 sangat urgent untuk memperbaiki proses pembelajaran di sekolah. Tulisan ini bertujuan mendeskripsikan framework dan prototype asesmen kompetensi Math-Sci untuk mengukur keterampilan abad 21. Metode penelitian pengembangan yang digunakan dalam penelitian ini mengacu pada framework Akker yang meliputi penelitian pendahuluan, prototipe yang meliputi desain, dan pengembangan dalam format paper and pencil test. Instrumen penelitian berupa lembar observasi, angket, dan tes. Hasil penelitian diperoleh kerangka konseptual instrumen dan prototipe asesmen kompetensi Math-Sci yang telah divalidasi melalui expert judgment. Kerangka konseptual asesmen kompetensi Math-Sci berupa soal-soal tematik, interdisipliner yang memadukan 3 (tiga) disiplin ilmu yakni IPA (Biologi-Fisika) dan Matematika pada konteks keIslaman. Math-Sci dengan analogi titian anak tangga (monodisiplin, interdisiplin 1, dan interdisiplin 2) yang mengukur kompetensi peserta didik secara hierarki mengacu pada proses berpikir taksonomi Bloom, konteks dan kompleksitas masalah. Hasil validasi pakar diperoleh instrumen soal yang dikembangkan valid dan layak. Pengembangan instrumen asesmen kompetensi Math-Sci merupakan langkah awal upaya menguatkan asesmen for learning, membantu memperbaiki pembelajaran, bersifat inovatif dengan menghadirkan permasalahan kontekstual integratif. How to Cite: Zulfiani, Suwarna, I.P., Suwarna, Muin, A. (2021). Framework and Prototype Development of Mathsci Instruments for Measuring 21st Century Skills in Islamic Context. TARBIYA: Journal of Education in Muslim Society, 8(1), 96-107. doi:10.15408/tjems.v8i1.22120.